Navigating Digital Political PR Law and Ethics: : A U.S.–Indonesia Comparison - Maryufani, Fathiyyah; Carl Jackson, Dean (Institut Komunikasi dan Bisnis LSPR, 2025)
This article examines the ethical and regulatory frameworks guiding political public relations (PR) in the United States and Indonesia through document analysis of professional codes and legal regulations. Comparing the PRSA Code of Ethics (U.S.) and the PERHUMAS Code (Indonesia), the study reveals key differences rooted in political and cultural contexts. PRSA emphasizes individual rights, transparency, and free speech, aligning with liberal-democratic values. In contrast, PERHUMAS prioritizes national interest, cultural harmony, and social stability, reflecting Indonesia’s collectivist and developmentalist orientation. Despite differing emphases, both codes lack specific ethical standards for political PR. This absence creates a grey zone where political communicators operate with limited guidance, risking the spread of disinformation, emotional manipulation, and public distrust. Regulatory documents in both countries also fall short: U.S. electoral laws focus on campaign finance and media fairness but overlook ethical conduct in strategic messaging. Indonesia’s regulations, while emphasizing national unity and public order, offer minimal oversight of political PR practices and are shaped by informal power structures. The findings show that both systems rely on voluntary compliance and self-regulation, with weak enforcement mechanisms. However, Indonesia’s context, marked by populism and digital transformation, makes the lack of clear ethical and regulatory frameworks particularly urgent. This article argues for the development of targeted ethical standards and stronger regulatory clarity to ensure accountability and uphold democratic values in political communication.